STEM BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR DAN SIKAP KOLABORASI SISWA KELAS V MATA PELAJARAN IPAS SD NEGERI 1 BINANGUN - Ramadhani, Irna Riskia; Muslim, Arifin (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to improve learning achievement and collaborative attitudes of fifth-grade students at SD Negeri 1 Binangun through the implementation of a STEM-based discovery learning approach. The research employed Classroom Action Research (CAR) with two cycles involving 21 students as research subjects. Data were collected using test instruments to measure learning achievement and non-test instruments to assess collaborative attitudes. Data analysis followed Miles and Huberman’s interactive techniques, including data collection, display, reduction, and verification. The results showed that the average learning achievement increased from 56.14 in cycle I, with 33.33% of students reaching mastery, to 71.8 in cycle II, with 80.95% achieving mastery. Meanwhile, collaborative attitudes based on adaptive indicators improved from 66.67% in cycle I to 85.71% in cycle II. It can be concluded that the implementation of a STEM-based discovery learning approach effectively enhances both learning achievement and collaborative attitudes of students.